Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pemustaka Di UPT Perpustakaan Universitas Negeri Surabaya - Muchammad Zuli Aryanto; Bambang Suratman (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
This research aims to determine the effect of service quality on user satisfaction at UPT library, Universitas Negeri Surabaya. This research uses five independent variable components namely tangible, reliability, responsiveness, assurance, and empathy with one dependent variable customer satisfaction. The sampling technique used was probability sampling using the Slovin formula obtained by respondents with a total of 180 students in the office administration education program. While the data collection techniques were carried out using, observation, interviews, and questionnaires using a Likert scale. This type of research is a quantitative approach. the method used. Data analysis methods used are validity and reliability test, classic assumption test, multiple linear regression analysis. The Results showed that there were (1) significant effect of service quality on user satisfaction; (2) there is a effect of service quality simultaneous on user satisfaction; (3) there is a effect of service quality partially on user satisfaction at UPT library, Universitas Negeri Surabaya.